Dielectric screening in perovskite photovoltaics - Rui Su (Nature Portfolio, 2021)
Performance of perovskite photovoltaics is greatly affected by undesirable defects that contribute to non-radiative losses. Here, the authors mitigate these losses by doping perovskite with KI to alter the dielectric response, thus defect capturing probability, resulting in inverted device with PCE of 22.3% and low voltage loss.